(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article explores Jane Austen's Sense and Sensibility as a reflection of early 19th-century English society, emphasizing themes of rationality versus emotion, gender dynamics, and class structure. It examines the nuanced characterization of the Dashwood sisters, who embody contrasting ideals, and Austen's critique of societal expectations. The study highlights Austen’s narrative techniques and the timeless relevance of her themes.